Quality and labeling of honey sold at markets in the Northern Coast of Rio Grande do Sul (Research, Society and Development, 2024)
The state of Rio Grande do Sul stands out nationally in beekeeping production, with farmers' markets being one of the main channels for distribution and trade of this product, allowing direct sales to consumers. However, it is known that honey is one of the most adulterated foods in the world. The objective of the study was to evaluate the compliance of honey sold at Farmers' Markets in the Northern Coast of Rio Grande do Sul. Physical-chemical parameters were assessed, such as moisture content, Water Insoluble Solids, and the presence of starch or dextrins using the Lugol Test. A labeling analysis was also conducted. A total of 51 samples from 9 markets in 5 municipalities in the region were evaluated. All honeys were considered genuine according to the Lugol Test. However, only 35% met the standard for moisture content (maximum 20%), and 90% were in compliance with the Water Insoluble Solids standard. Only 25.49% of the samples passed all the physical-chemical parameters analyzed. Regarding labeling, less than half of the samples (49%) had labels and met all requirements, such as product origin, food safety, and nutritional information. The Consumer Service item was absent from all samples, and the list of ingredients appeared in only one-third of the samples. It was concluded that although no adulteration of honey was detected, most did not meet all the required quality and labeling standards. Greater control and inspection are necessary to offer consumers a quality and reliable product.